Understanding earth's polar challenges: International Polar Year, 2007-2008;summary by the IPY Joint Committee - ICSU/WMO Joint Committee for International Polar Year 2007-2008; Krupnik, Igor (CCI Press, 2011)
Co-published by the University of the Arctic Incl. bibl.